Stromal Fibroblasts Counteract the Caveolin-1-Dependent Radiation Response of LNCaP Prostate Carcinoma Cells - Wittka, Alina; Ketteler, Julia; Borgards, Lars; Maier, Patrick; Herskind, Carsten; Jendrossek, Verena; Klein, Diana (Frontiers in Oncology, 2022)
In prostate cancer (PCa), a characteristic stromal-epithelial redistribution of the membrane protein caveolin 1 (CAV1) occurs upon tumor progression, where a gain of CAV1 in the malignant epithelial cells is accompanied by a loss of CAV1 in the tumor stroma, both facts that were correlated with higher Gleason scores, poor prognosis and pronounced resistance to therapy particularly radiotherapy (RT). However, it needs to be clarified whether inhibiting the CAV1 gain in the malignant prostate epithelium or limiting the loss of stromal CAV1 would be the better choice for improving PCa therapy, particularly for improving the response to RT; or whether ideally both processes need to be targeted. Concerning the first assumption, we investigated the RT response of LNCaP PCa cells following overexpression of different CAV1 mutants. While CAV overexpression generally caused an increased epithelial-to-mesenchymal phenotype in respective LNCaP cells, effects that were accompanied by increasing levels of the 5′-AMP-activated protein kinase (AMPK), a master regulator of cellular homeostasis, only wildtype CAV1 was able to increase the three-dimensional growth of LNCaP spheroids, particularly following RT. Both effects could be limited by an additional treatment with the SRC inhibitor dasatinib, finally resulting in radiosensitization. Using co-cultured (CAV1-expressing) fibroblasts as an approximation to the in vivo situation of early PCa it could be revealed RT itself caused an activated, more tumor-promoting phenotype of stromal fibroblasts that was charachterized by an increased metabolic potential, which could not be limited by combined dasatinib treatment. Thus, targeting fibroblasts and/or limiting fibroblast activation, potentially by limiting the loss of stromal CAV1 seems to be absolute for inhibiting the resistance-promoting CAV1-dependent signals of the tumor stroma.